THE LONG-TERM EFFECTS OF CONTRACEPTIVE METHODS ON UTERINE MORPHOLOGY AND HISTOPHYSIOLOGY (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
The long-term effects of contraceptive methods on the morphology and histophysiology of the uterus are among the most relevant topics in reproductive health and medical research. This article explores the morphological and histophysiological characteristics of the uterus and analyzes the structural changes caused by prolonged use of various contraceptive methods. The impact of hormonal contraceptives, intrauterine devices (IUDs), and progesterone-based contraception on the endometrial lining, myometrium, and overall reproductive function is examined. Modern diagnostic and research methods for assessing the long-term positive and negative effects of contraceptive methods are discussed. These studies contribute to the development of safe and effective contraception strategies for women's health.